Primary cutaneous precursor B cell lymphoblastic lymphoma in a child, complicated by fatal disseminated varicella zoster virus. (9th May 2015) - Rashidghamat, E.; Robson, A.
Summary: Precursor B‐cell lymphoblastic lymphoma (PBLL) is a rare subtype of childhood non‐Hodgkin lymphoma (NHL). Most lymphoblastic lymphomas have a T‐cell immunophenotype, but a small distinct proportion is of precursor B‐cell origin. Skin and bone involvement is seen more commonly in this clinical variant. Primary cutaneous PBLL is rare. We describe an 8‐year‐old girl who presented with an asymptomatic nodule on the left upper arm. Histopathological features were consistent with pre‐B‐cell lymphoblastic lymphoma, and staging investigations excluded extracutaneous disease, resulting in a diagnosis of primary cutaneous PBLL. The child was started on induction chemotherapy, UKALL 2003 regimen B. She developed disseminated varicella zoster virus and died despite treatment. We discuss previously reported cases of primary cutaneous PBLL and their outcomes.